Accessible ring opening metathesis and atom transfer radical polymerization catalysts based on dimethyl sulfoxide ruthenium(II) complexes bearing N-heterocyclic carbene ligands - Idehara, André H.S. [UNESP]; Gois, Patrik D.S. [UNESP]; Fernandez, Henrique; Goi, Beatriz E. [UNESP]; Machado, Antonio E.H.; Lima-Neto, Benedito S.; Carvalho, Valdemiro P. [UNESP] (Elsevier, 2018)
Dimethyl sulfoxide ruthenium(II) complexes of N-heterocyclic carbenes derived from cycloalkylamines (cycloalkyl = cyclopentyl (1a), cyclohexyl (1b), cycloheptyl (1c), and cyclooctyl (1d)) were synthesized: [RuCl2(S-dmso)2(IPent)] (2a), [RuCl2(S-dmso)2(IHex)] (2b), [RuCl2(S-dmso)2(IHept)] (2c), and [RuCl2(S-dmso)2(IOct)] (2d). The imidazolium salts 1a-1d were characterized by FTIR, UV–vis, and 1H and 13C NMR spectroscopy, while their respective dimethyl sulfoxide ruthenium(II) complexes (2a-2d) were characterized by elemental analysis, FTIR, UV–vis, 1H and 13C NMR, and cyclic voltammetry. The complexes 2a-2d were evaluated as catalytic precursors for ROMP of norbornene (NBE) and for ATRP of methyl methacrylate (MMA). The polynorbornene (polyNBE) syntheses via ROMP using the complexes 2a-2d as pre-catalysts were evaluated under reaction conditions of [EDA]/[Ru] = 28 (5 μL), [NBE]/[Ru] = 5000 at 50 °C as a function of time. The polymerization of MMA via ATRP was conducted using the complexes 2a-2d in the presence of ethyl 2-bromoisobutyrate (EBiB) as the initiator. All tests were using the molar ratio [MMA]/[EBiB]/[Ru] = 1000/2/1 and conducted at 85 °C. The linear correlation of ln([MMA]0/[MMA]) and time clearly indicates that the concentration of radicals remains constant during the polymerization and that the ATRP of MMA mediated by 2a-2d proceeds in a controlled manner.
Keywords: ATRP; Methyl methacrylate; Norbornene; ROMP; Ruthenium complexes